DIPG-58. SUBTYPE-SPECIFIC OVEREXPRESSION OF WILMS' TUMOR PROTEIN IN PEDIATRIC MIDLINE HIGH GRADE GLIOMAS. Issue 2 (22nd June 2018) - Lee, Sulgi; Kambhampati, Madhuri; Yadavilli, Sridevi; Santi, Mariarita; Packer, Roger J; Cruz, Conrad R; Almira, Isabel; Hwang, Eugene; Nazarian, Javad
Abstract: Midline pediatric high grade gliomas (HGGs), especially diffuse intrinsic pontine gliomas (DIPGs), are deadly pediatric brain cancer that makes up 10–15% of all central nervous system (CNS) tumors in children; little progress has been made in improving outcomes for these patients. Immunotherapy is a strategy that has shown promise for treatment of malignancy, although identification of tumor associated antigens is critical to an effective immunotherapeutic approach. Wilms' tumor protein (WT1) has been heavily implicated in cancer development, and it may serve as an attractive immunotherapy target in HGGs. Here, we validated WT1 as a potential tumor associated antigen in pediatric midline gliomas using formalin fixed paraffin embedded (FFPE) tumor, intra-patient healthy tissue controls, fresh frozen post-mortem tissues, and patient-derived DIPG primary cell lines. Immunohistochemical staining of patient FFPE specimens showed strong WT1 immunoreactivity in tumor compared to adjacent healthy tissue controls. Western blot of tumor further validated higher WT1 levels in tumor versus adjacent normal tissues. Tumor showed cytoplasmic expression of WT1, confirmed by immunofluorescent (IF) staining. In addition, a striking dichotomy of expression was noted with absent/weak WT1 immunoreactivity in H3.1K27M subtype gliomas, compared to moderate/strong signal in H3.3K27M subtypes. Western blotting assay and reverse transcription quantitative PCR using DIPG primary cell lines also validated the differential expression of the protein. Our study suggests that WT1 is an attractive potential target protein for pediatric midline glioma immunotherapy and may differentiate between the underlying histone mutations.